Sailing Ship Technology, Navigation and the Duration of Voyages to Australia, 1848-85 - Timothy J. Hatton (Institute of Labor Economics (IZA), 2024)
Sailing ships persisted on emigrant voyages to Australia until the late nineteenth century and passage durations decreased by three weeks from the late 1840s to the mid-1880s. The shortening of voyages by sail has been linked to improvements in navigation and in sailing ship technology but without quantitative estimates. Analysis of 311 voyages of emigrant ships that sailed directly from a UK port to Adelaide from 1848 to 1885 shows that the decline in voyage duration was associated with increases in tonnage, iron construction and, above all, clipper-style ship design. Advances in ship technology also enabled captains to take fuller advantage of sailing the so-called great circle route to Australia. Examining a unique dataset of the tracks of 290 voyages from Europe to Melbourne in 1854-62, I find that larger and clipper-style ships reduced voyage durations, both directly, because they were faster on a given track, and indirectly, because they could better exploit the great circle route.
Keywords: F22; N77; O33; 330; colonial Australia; sailing ships; voyage durations